TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION IN ISLAMIC BOARDING SCHOOLS THROUGH THE INTEGRATION OF ISLAMIC DIGITAL ETHICS VALUES - Faid Kholid; Fathor Rozi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study explores the transformation of Islamic Religious Education (PAI) through the integration of Islamic Digital Ethics values at Pesantren Syamsul Jinan, Besuki, Situbondo. The research aims to describe how pesantren, as traditional Islamic educational institutions, adapt to the digital era without losing their spiritual and moral foundations. Using a qualitative descriptive approach with field research methods, data were collected through interviews, observation, and documentation involving kyai, teachers, and students.The findings reveal that Pesantren Syamsul Jinan has successfully implemented digital-based learning innovations such as the use of multimedia tools, Islamic digital applications, and online learning systems. However, these developments are always accompanied by the internalization of Islamic values such as honesty, responsibility, and digital ethics based on the principle of adab al-ma‘lumat (ethics of information). Teachers play a central role in guiding students to apply ethical principles in digital interactions and to use technology as a medium of da’wah and learning. The integration of Islamic Digital Ethics in the pesantren’s PAI learning process contributes significantly to the moral development of students, ensuring that technological advancement supports—rather than undermines—their Islamic character. Challenges such as limited digital facilities and variations in teachers’ technological skills still exist, but the institution continues to strengthen digital literacy and ethical awareness. This study concludes that Pesantren Syamsul Jinan represents a model of adaptive Islamic education, combining traditional pesantren values with modern technological competencies. The results of this research are expected to serve as a reference for other Islamic boarding schools in integrating digital transformation with Islamic ethics, forming a generation of students who are digitally literate, morally grounded, and spiritually intelligent.